Bosnia and Herzegovina : from recovery to sustainable growth - World Bank. (Washington, D.C. : World Bank, 1997)
Bosnia and Herzegovina are experiencing the beginnings of political, social and economic recovery. The challenge is to build up the Dayton-mandated institutions and to make the economic recovery sustainable with the help of the international community. This book discusses this challenge
Includes bibliographical references
Keywords: Yugoslav War, 1991-1995 -- Destruction and pillage -- Bosnia and Herzegovina; Postwar reconstruction -- Bosnia and Herzegovina